WNT/β-Catenin Signaling Pathway Regulating T Cell-Inflammation in the Tumor Microenvironment - Li, Xin; Xiang, Yanwei; Li, Fulun; Yin, Chengqian; Li, Bin; Ke, Xisong (Frontiers in Immunology, 2019)
Immunotherapy with checkpoint inhibitors has greatly prolonged the overall survival of cancer patients in melanoma and many other cancer types. However, only a subset of patients shows clinical responses from these interventions, which was predicated by the T cell-inflamed tumor microenvironment. T cell-inflamed phenotype is characterized by the infiltration of CD8+ T cells, CD8α/CD103-lineage dendritic cells (DCs), as well as high density of FoxP3+ Regulatory T cells (Tregs) that are associated with the efficacy of immune checkpoint blockade. A number of regulators has been associated with T cell-inflammation in tumor microenvironment, and WNT/β-catenin signaling is one of the best characterized. The tumor-intrinsic WNT/β-catenin signaling activation is frequently associated with poor spontaneous T cell infiltration across most human cancers. In this article, we will review the essential roles of WNT/β-catenin signaling in the T cell-inflamed and non-T cell-inflamed tumor microenvironment, including the development and function of immune cells, activation of immune exclusion of tumor cells, and cancer immunosurveillance. We also discuss the impact of this pathway in driving the non-T cell-inflamed tumor microenvironment in other tumor types. To improve immunotherapy efficacy, we argue that targeting Wnt/β-catenin signaling pathway should be a high priority for combinational cancer therapy to restore T cell infiltration.